2019
DOI: 10.1002/lt.25614
|View full text |Cite
|
Sign up to set email alerts
|

Liver Imaging Reporting and Data System Version 2018: Impact on Categorization and Hepatocellular Carcinoma Staging

Abstract: The purpose of this study was to assess the concordance in categorization and radiologic T staging using Liver Imaging Reporting and Data System (LI‐RADS, LR) version 2017 (v2017), version 2018 (v2018), and the Organ Procurement and Transplantation Network (OPTN) criteria. All magnetic resonance imaging and computed tomography reports using a standardized LI‐RADS macro between April 2015 and March 2018 were identified retrospectively. The major features (size, arterial phase hyperenhancement, washout, enhancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…4). However, this affects <1% of all LR‐3 and LR‐4 and only 2% of LR‐5 observations 9 …”
Section: Changes In Li‐rads V2018mentioning
confidence: 97%
“…4). However, this affects <1% of all LR‐3 and LR‐4 and only 2% of LR‐5 observations 9 …”
Section: Changes In Li‐rads V2018mentioning
confidence: 97%
“…6 The price of high specificity of LR-5 category is its modest sensitivity, ranging between 50% and 80%. [16][17][18] Nonrim APHE and size 10 mm are required for LR-5 categorization, that is, observations <10 mm or lacking nonrim APHE cannot be categorized LR-5, regardless of any other imaging features. 3 The LR-5 category includes observations >20 mm with 1 additional major feature and 10 to 19 mm observations with 2 additional major features.…”
Section: Lr-5: Definitely Hccmentioning
confidence: 99%
“…4 The new LR-5 criteria result in upcategorization of approximately 40% of LR-4 observations based on v2017. 16 However, several studies had demonstrated improved sensitivity and accuracy of the v2018 LR-5 category as compared with v2017 for the diagnosis of HCC. [16][17][18] For patients with LR-5 observations, multidisciplinary discussion is needed for staging and optimal treatment.…”
Section: Lr-5: Definitely Hccmentioning
confidence: 99%
“…Ninety-four percent of observations in this category are HCC and 97% are malignant [17] . Since HCC can be diagnosed based on imaging features alone and treated without the need for pathologic confirmation, observations in this category have specificity close to 100% with resulting modest sensitivity in the range of 50%-80% [21][22][23] . Size ≥ 10 mm and nonrim APHE are absolute requirements to LR-5 categorization [7,15] .…”
Section: Lr-5: Definitely Hccmentioning
confidence: 99%